On the AdS 3 Virasoro-Shapiro amplitude - Luis F. Alday; Gaston Giribet; Tobias Hansen (Journal of High Energy Physics)
Abstract We consider tree-level scattering amplitudes for four string tachyons on AdS 3 × N $$ \mathcal{N} $$ with pure NSNS fluxes. We show that in a small curvature expansion, properly defined, the amplitudes take the form of a genus zero integral given by the Virasoro-Shapiro integrand with the extra insertion of single valued multiple polylogarithms. This is the same structure as the one found for the AdS Virasoro-Shapiro amplitude in higher dimensions.